Idiosyncratic Drug-Induced Liver Injury in a Healthy Patient following PCSK9-Inhibitor Injection - B.-O. Stüben; D. P. Hoyer; S. Radunz; F. Saner; H. Schmidt; H. A. Baba; J. W. Treckmann; L. I. Mazilescu (Case Reports in Hepatology)
Background. Acute liver injury is a life-threatening condition with disparate aetiology. Swift and adequate interdisciplinary treatment is essential to assure the best possible outcomes in these patients. Investigations to identify the cause of the condition and the implementation of quick and appropriate treatment can be lifesaving. Case Presentation. In October 2022, an otherwise healthy 66-year-old male presented at the University Hospital Essen with acute liver injury following an inclisiran injection for hypercholesterinaemia. Four weeks following admission, the patient fully recovered after initially receiving short-term cortisol therapy and open albumin (OPAL) dialysis, and the indices of liver, kidney, and coagulation function were normal at discharge. Conclusion. This is to our knowledge the first reported acute liver injury due to an inclisiran injection. Cortisol in combination with OPAL dialysis is an effective method for the treatment of acute liver injury caused by inclisiran injury, and in this case, it led to a near-complete reversal of the acute liver injury at the time of discharge.